Active futures: combating youth sedentary lifestyles in Pakistan through smart use of fragmented time - Aslam, Sumaira; Bin, Shi Yong (Frontiers in Sports and Active Living, 2025)
Sedentary behavior among adolescents is a growing concern globally, including in Pakistan, due to its association with negative physical and psychological health outcomes. Fragmented time agility training has arisen as a prospective solution to tackle these challenges. The proposed work evaluates the impact of a structured six-week agility training protocol on sedentary behavior, mood, and stress among adolescents aged 12–18 in Pakistan. A total of 100 participants (50 intervention, 50 control) were recruited from three schools in Islamabad, with equal representation of males and females. Participants were randomly assigned to an intervention group that completed daily 30-min agility training sessions (including high-knee running, lateral shuffles, and cone drills, five days a week) or a control group that maintained their usual routines. Sedentary behavior (sitting and screen time), mood [Profile of Mood States (POMS)], and stress levels [Perceived Stress Scale (PSS)] were assessed at baseline and post-intervention. Differences between groups were analyzed using independent t-tests. At post-intervention, significant between-group differences were observed. The intervention group showed reductions in sitting time (6–4 h/day, p < 0.001) and screen time (4–2.5 h/day, p < 0.001) equated to the control group. Mood improvements were noted with decreased tension and fatigue and increased vigor (p < 0.01 for all). Stress levels in the intervention group decreased significantly from 31 to 24 (p < 0.001), though no notable alterations were detected in the control group. Concise, systematically organized agility-oriented training significantly diminishes sedentary behavior while concurrently improving psychological well-being in adolescent populations. This adaptable and economically feasible intervention provides critical insights for public health initiatives focused on mitigating sedentary lifestyles and addressing mental health issues among young individuals, especially in contexts with limited resources.